Masterpieces of Italian design - Fiell, Charlotte 1965-; Fiell, Peter; Rossi, Catharine 1982- (Goodman Fiell, 2013)
Design in Italy has always reflected the national identity of the Italians themselves: sexy, stylish and with more than a touch of audacity. No other country takes design so seriously, nor treats its practitioners with such reverence. There is a strongly held belief that good design should be implemented passionately and comprehensively across all aspects of life--or as the architect Ernest Rogers put it, "from the spoon to the city". Masterpieces of Italian Design is an overview of the past two centuries in Italian design and manufacturing, documenting the 100 most pioneering designs to come out of Italy, using stunning images and informative texts to explain the significance of these masterpieces." -- Provided by publisher